An Experience of the Application of Glossaries and Wikis for Collaborative Learning of the Materials Science Subject - Eliche-Quesada, Dolores; La Rubia, M. Dolores; Martinez-Cartas, M. Lourdes (IEEE-RITA, 2021)
In this study, wikis and glossaries as complementary and optional tools to develop an active methodology based on online peer-learning with the objective of promoting active participation, the acquisition of competences and improving in the teaching-learning process, as well as, the academic performance in the subject Materials Science of the Chemistry Degree of the students' self-learning during two academic years. Making use of the learning management system ILIAS, a collaborative learning environment has been created by and for students. The problems found in the experience carried out during the first academic year have been described. The analysis and corrective actions carried out have allowed more satisfactory results to be obtained during the following academic year in which this methodology was applied. Students have been asked a questionnaire to find out their perception of the competences they consider to have consolidated and / or developed with the collaborative work carried out. The impact of the implementation of collaborative learning methodology on the academic performance of students has been obtained through the analysis of academic results The implication of students has contributed successfully to the acquisition of competences and self-learning, providing them with more control over their own learning process.